Assignment of chromosome rearrangements between X chromosomes of human and cattle by laser microdissection and Zoo-FISH - Rubes, Jiri; Kubickova, Svatava; Musilova, Petra; Amaral, M Elisabete; Brunner, Ronald M; Goldammer, Tom (Chromosome research, 2005)
Cross-species fluorescence in-situ hybridization (Zoo-FISH) was performed on cattle metaphase spreads using Homo sapiens X chromosome (HSAX) painting probes specific for the p- and q-arms to identify the cytogenetic location of a chromosome breakpoint between HSAX and the Bos taurus X chromosome (BTAX). The existence of a breakpoint is strongly suggested by recent radiation hybrid and FISH mapping results. Hybridization probes were generated by microdissection of HSAX p- and q-arms using the contact-free technology of Laser Microdissection and Pressure Catapulting (LMPC), amplification of the isolated chromosome material by DOP-PCR, and labelling of the PCR products with digoxigenin in a secondary PCR. Independent Zoo-FISH of the two painting probes on bovine metaphase chromosomes (detected by antidigoxigenin-fluorescein) resulted in clear hybridization signals on BTAX. A breakpoint was identified between HSAXp and HSAXq on BTAX, and narrowed down between the G-bands BTAXq25 and BTAXq26. The assumed centromere transposition between HSAX and BTAX associated with the rearranged chromosome segments is supported by cytogenetic assignments of the genes BGN and G6PD to BTAX.
Keywords: lasery; Cattle; sekvence nukleotidů; Chromosomes, Human, X; karyotypizace; Lasers; hybridizace in situ fluorescenční; skot; Karyotyping; DNA Primers; chromozom X; lidské chromozomy X; X Chromosome; Animals; lidé; Humans; zvířata; DNA primery; In Situ Hybridization, Fluorescence; Base Sequence